Scaffolding online learning in a higher education institution: a need analysis / Lee Yee Ling - Lee, Yee Ling (A Peer-Reviewed Journal Published Uitm Press, 2022)
The COVID-19 pandemic has changed the learning landscape at higher education institutions worldwide. University students face many challenges, adapting to online learning instantly. It is necessary to provide adequate scaffolds to students when they learn online. However, a literature review revealed that scaffolds were designed based on the literature or teachers' conceptualisation of scaffolding. Need analysis for scaffolding is under-researched. This action research aimed to investigate the challenges faced by postgraduate students during online learning and the types of scaffolds they needed for online learning. This research involved 35 postgraduate students in a private higher education institution. The participants completed an online questionnaire. Data was coded and categorised into themes. The results showed that the students faced various challenges in terms of personal competency, language proficiency, assessment and learning resources. They needed support from fixed scaffolds and adaptive scaffolds. Based on the results from the baseline study, the researcher designed multiple forms of scaffolds to support online learning. This study highlights the need to design scaffolds based on student's learning needs to address the challenges they face in an online learning context. Limitations in terms of data collection method and instruments are discussed. Although the challenges explained by the students may only represent the period of campus closure, this research provides insights into students' perceptions of scaffolding in a unique period in higher education. The findings contribute to the design of scaffolding in the online learning context.